Pengembangan Bisnis Physa Tea sebagai Produk Herbal Berbasis Ciplukan (Physalis angulata L.) - Audyningtyas, Keyra Regina; Renaldi, Eddy (Universitas Galuh, 2026)
Indonesia has various types of local plants that have great potential as raw materials for herbal products. Research on ciplukan (Physalis angulata L.) as a raw material for herbal products shows promising results. Physa Tea is a herbal product made from ciplukan, developed to provide a natural health solution, especially for controlling blood sugar levels. This study aims to analyze the business potential of Physa Tea. The method used in this research is the Lean Startup Methodology. Primary data were obtained through semi-structured interviews with 20 consumer informants and key informants (the product development team). In the Build stage, the product was made to get feedback from consumer informants. The Measure stage involved collecting feedback to assess market acceptance of the product. The results from the Learn stage were used to improve the product based on the feedback. This research shows that Physa Tea has good market potential, especially among consumers who care about health and blood sugar control. The findings are expected to serve as a basis for sustainable product planning in developing this herbal product.